IMPACT OF DIGITAL EDUCATION ON HUMAN COGNITIVE ABILITY (TAMADDUN NURI JURNALI, 2025)
The article examines the impact of digital education on human cognitive abilities such as memory, attention, and thinking. The results of a study conducted among students who studied using digital technologies and traditional methods are presented. The advantages of digital education, including the development of short-term memory and creative thinking, as well as its disadvantages, such as decreased long-term memory and concentration, are revealed. The conclusion is made about the need for a balanced use of digital and traditional approaches to improve the effectiveness of learning.